2018
DOI: 10.1093/mnras/sty1954
|View full text |Cite
|
Sign up to set email alerts
|

MORGOTH: incorporating horizontal branch modelling into star formation history determinations

Abstract: We present a new method that incorporates the horizontal branch morphology into synthetic colour-magnitude diagram based star formation history determinations. This method, we call MORGOTH, self-consistently takes into account all the stellar evolution phases up to the early asymptothic giant branch, flexibly modelling red giant branch mass loss. We test MORGOTH on a range of synthetic populations, and find that the inclusion of the horizontal branch significantly increases the precision of the resulting star … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…Finally, we note that the absolute age scale of the SFH in Sculptor is uncertain, and is currently being debated. Weisz et al (2014) and Bettinelli et al (2019) derived a much shorter SFH in Sculptor (∼3 Gyr), than was reported by Savino et al (2018), and than we adopted here ( Fig. 1; de Boer et al 2012a).…”
Section: Chemical Clocks In Different Environmentssupporting
confidence: 58%
“…Finally, we note that the absolute age scale of the SFH in Sculptor is uncertain, and is currently being debated. Weisz et al (2014) and Bettinelli et al (2019) derived a much shorter SFH in Sculptor (∼3 Gyr), than was reported by Savino et al (2018), and than we adopted here ( Fig. 1; de Boer et al 2012a).…”
Section: Chemical Clocks In Different Environmentssupporting
confidence: 58%
“…In particular, the gas-to-dust ratio used results in a very conservative, low value, of the RGB mass loss. The mass loss relation in the Sculptor dSph has been obtained by Salaris et al (2013) and Savino et al (2018) using an analogous approach to this work. The two measurements also show some differences.…”
Section: The Rgb Mass Lossmentioning
confidence: 99%
“…We model the CMD using MORGOTH (Savino et al 2018). MORGOTH is a SFH recovery method that uses synthetic CMDs to model all the evolutionary phases up to the beginning of the thermally pulsating asymptotic giant branch.…”
Section: The Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…HB stars offer a uniquely luminous insight into the most ancient stellar populations in a galaxy, and it has recently been shown that they can offer a more accurate look at how star formation rates and metallicity varied at the earliest times (Salaris et al 2013;Savino et al 2015Savino et al , 2018. It is clear that the HBs in nearby galaxies all look different (see Figure 4), revealing a variety of early SFHs even in the smallest dwarf galaxies, even more so than had previously been envisaged (Savino et al, in prep).…”
Section: Ancient Main Sequence Turnoffsmentioning
confidence: 99%